Social perception of childhood overweight and obesity to generate prevention strategies in Nuevo León, Mexico. - García González, Janet; Picazzo Palencia, Esteban; Cortés Hernández, Dora Elia; Silva Aguilar, Kabáh (Universidad Juárez Autónoma de Tabasco, 2015)
To determine the social perception on childhood overweight and obesity for the purpose of generating communication strategies that would prevent it through changes in behavior. A descriptive study using a qualitative research method that involved focus groups with children, teachers and parents. The type of analysis was argumentative. The study was conducted from January to May 2013 in the metropolitan area of Monterrey, Nuevo León, Mexico.